The Value of a Thousand Suluks as a Foundation for MSME Taxpayer Compliance Registered in Rokan Hulu Regency - Nurhayati, Nurhayati; Sembiring, Boy Jerry (Accounting and Business Journal, 2023)
Research objectives foranalyze the effect of Tax Morale and Taxpayer's Religious Value Simultaneously on MSME Taxpayer Compliance registered in Rokan Hulu Regency.Quantitative research is a research method based on positive philosophy, used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative/statistical in nature, with the aim of testing established hypotheses.the determined sample method is not random (non-probability sampling) with a sampling technique that is purposive sampling of 67 samples. The results of the study show that taxation morale has a significant effect on taxpayer compliance,Religious Value has a significant effect on taxpayer compliance and Tax Morale and Religious Value simultaneously have a significant effect on taxpayer compliance.